Empowering visually impaired students through innovative tools and accessible waste sorting education at the national level - Patranit Srijuntrapun; Issavara Sirirungruang; Chawalit Nucharoen (PLoS ONE, 2025)
Waste separation is a critical strategy to address the intensifying global waste crisis. However, inclusive teaching strategies for visually impaired students remain limited. This study addresses this pressing gap by implementing an innovative intervention rooted in experiential learning principles. This approach integrates sound-equipped bins and waste sorting activity guides tailored to empower visually impaired students to independently and effectively separate waste. The research study employed a mixed-methods design encompassing three key phases: (1) training teachers to proficiently use accessible tools and to deliver comprehensive waste management education, (2) training visually impaired students through hands-on experiential learning to develop independent waste separation skills, and (3) evaluating behavior changes and skill retention among students after the training. The results demonstrated significant statistical improvements in knowledge (mean increase = 0.74, p < 0.001), attitudes (mean increase = 0.50, p < 0.001), and practical skills (mean increase = 0.55, p < 0.001) by students. These findings highlight the transformative potential of inclusive educational innovations to bridge existing gaps and promote self-reliance in waste separation among visually impaired learners. The study emphasizes the importance of adopting creative, evidence-based strategies to ensure inclusivity and sustainability in environmental education on a global scale. Policymakers and educators are urged to leverage these insights to advance environmental literacy and foster equitable participation in waste management practices.